Effects of erythromycin on stretch-induced contractile activity of isolated myometrium from pregnant women - Celik, H; Ayar, A; Sapmaz, E (Wiley, 2001)
Background. Despite the fact that preterm labor and birth account for the vast majority of neonatal morbidity and mortality the currently available treatment options are still far from satisfactory. The aim of this study was to investigate the effects of erythromycin on stretch-induced contractions of pregnant human myometrial strips, obtained at cesarean section. Method. Myometrial strips were suspended in an organ bath under 3 g tension and the effects of erythromycin (0.1, 0.2, 0.5, 1.0 mM) on stretch-induced isometric contractions were evaluated. Results were statistically analyzed using Kruskal Wallis analysis of variance and Wilcoxon Rank tests where appropriate. Results. Erythromycin caused a significant decrease in the peak amplitude, while causing an increase in frequency of stretch-induced myometrial contractions in a dose dependent manner in vitro. Conclusions. Results from this preliminary study suggest that erythromycin may have additional beneficial effects in infection related preterm labor cases, however, further studies are needed for clarifying the usefulness of erythromycin as a tocolytic agent.
Keywords: erythromycin; human pregnancy; myometrium; stretch-induced contraction